Teaching Factory Management for Entrepreneurial Competency Development: A Case Study Analysis Using Terry's POAC Framework - Dede Supriadi; Okke Rosmaladewi (Papanda Publisher, 2026)
Vocational education in the Fourth Industrial Revolution requires graduates with entrepreneurial competencies, yet Teaching Factory (TeFa) implementation in BLUD vocational schools remains suboptimal. This study examined TeFa management effectiveness in developing students' entrepreneurial competencies through George R. Terry's management framework (planning, organizing, actuating, controlling). A qualitative case study design was employed at SMKN 1 Pangandaran and SMKN 1 Banjar, Indonesia, involving 24 participants including principals, teachers, BLUD managers, industry partners, and students. Data were collected through in-depth interviews, participatory observations (120 hours), and document analysis over six months (March-August 2024). Analysis followed Miles, Huberman, and Saldaña's interactive model with multiple triangulation strategies. Results revealed that while TeFa programs successfully enhanced students' technical and soft skills, entrepreneurial competency development remained inadequate across all management functions. Planning lacked comprehensive industry collaboration and entrepreneurship frameworks; organizing operated informally without standardized SOPs; implementation focused predominantly on technical skills; and controlling mechanisms neglected multidimensional entrepreneurial assessment. These deficiencies reflect insufficient teacher preparation, weak industry partnerships, and absent comprehensive evaluation frameworks. The study concludes that effective entrepreneurship-oriented TeFa requires formalized industry collaboration in planning, standardized SOPs, pedagogically sophisticated implementation integrating entrepreneurship throughout instruction, and validated multidimensional assessment systems. Findings contribute theoretical insights on implementation fidelity while offering practical recommendations for vocational education policy and management reform.